If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 47 + -11 = 36 Combine like terms: 47 + -11 = 36 36 = 36 Add '-36' to each side of the equation. 36 + -36 = 36 + -36 Combine like terms: 36 + -36 = 0 0 = 36 + -36 Combine like terms: 36 + -36 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 2(12.5-4x)+2x=11.5 | | 9-16y^2=0 | | 42/0.2 | | 5(7a-8)=-320 | | 12z=168 | | 2(12.5-4x)+2y=11.5 | | 4y+2.6y=36 | | 2x+7=x+7+x | | 3x-2sin(x)+7=0 | | (a-bi)(3+5i)=0 | | 9x^3-6x^2-6x+4=0 | | 2(w+3)-8w-1= | | 5x+14=4+3x | | 7(b-4)=-84 | | 3z+20=(-55) | | x-x*.17=24070 | | 7x-4+2x=5 | | n-16=21 | | 8(2n+6)=112 | | 8.304/16 | | 4x+10-6+4=20 | | 2/5x=6/35 | | 2xsquare=8x | | 4(6-5x)=164 | | -8w+10=5 | | 2(3x-18)=0 | | P(X)=x^3-4x^2+8 | | -2xa+4a=0 | | 0.5/8= | | -6m-9n=0 | | 7y-5=16 | | 4(1-3n)=88 |